Prevalence of Low Birth Weight among Normal Singleton Low Risk Pregnancies at a Tertiary Care Teaching Hospital in India - Reddy V, Manikanta; V, Vallishri; R, Umadevi; Manasa A, Krishna; Rani S, Teresa; Devi G, Prameela; Chaitanya Reddy D, Krishna (Journal of Neonatal Surgery, 2025)
Introduction: Birth weight is an accurate indicator of neonatal wellbeing alongside gestational age and congenital of newborn. Low birth weight (LBW) (< 2500gms) is associated with neonatal mortality and variety of morbidities such as cerebral palsy, motor delays, growth retardation, psychological problems and is becoming a significant global health crisis. The relationship between LBW and abnormalities of placenta/umbilical cord remains largely unexplored. Therefore, it is imperative need for multidimensional exploration to comprehend the LBW. The objective of the study was to determine the prevalence of LBW among neonates born to low risk singleton mothers and to analyze its association with selected maternal and neonatal factors. Methodology: This cross-sectional study analyzed 300 antenatal records of low-risk singleton pregnancies. Maternal demographic and clinical variables, including age, gravidity, history of abortion, and hemoglobin levels, were collected. Neonatal data included birth weight, gestational age at delivery, and sex. Data was analyzed using SPSS 20.0 software. Continuous variables were presented as mean with standard deviation. Categorical variables were presented into proportions. Chi-square test was applied to find out the association between LBW and preterm births. P value<0.05 at 95% confidence interval was considered statistically significant. Results: The mean maternal age was 24.19 ± 4 years, and the mean hemoglobin level was 10.86 ± 1.4 g/dL. Of the mothers, 35.7% were primigravida and 19.7% had a history of abortion. Among the neonates, 47% were male and 53% female, with a mean birth weight of 2801.6 ± 489.2 grams. Preterm births accounted for 16.3% of deliveries. The prevalence of LBW was 16.3% (n = 49), including 1.6% (n = 5) who were very low birth weight (<1500 grams). LBW was significantly associated with preterm birth (χ²(1) = 65.414, p < 0.05), while no significant association was found with prior abortion history (p = 0.353) or neonatal sex (p = 0.747). Conclusion: The prevalence of low birth weight (LBW) in our study was remarkably higher at 16.3% considering the exclusive recruitment of low risk singleton pregnancies. Despite the higher incidence of LBW, the rate of very low birth weight (VLBW) was lower at 1.6%.